Full Day School Ala Pendidikan Islam Pesantren (Telaah Pembelajaran Pesantren dari Hulu hingga Hilir) - Ahmad Khori (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: Education in boarding school is closely related to the issue of full day school that discussed on the national discourse. The learning process is carried out in boarding schools, studied conducted by the students to the study the book done by clerics, cultivate character and attitude tawadu ‘to teachers/kyai who give birth blessing as students live the live in the future. The methodology used is the study of literature with literature review historical beginnings of Islamic education/schools of archaeologist, local kingdoms, the Waliyullah era, until today. Result of Islamic education is expected to equip the students looking to the future with high confidence, through, remembrance, and the righteous deeds are the primary capital to face brighter future. Keywords: Fullday, Islamic Education, Pesantren.